Evaluación de cuatro tipos de mulch orgánico para recuperar suelos erosionados en el cultivo de remolacha (Beta vulgaris L.) en el sector Salache, cantón Latacunga, provincia Cotopaxi 2021. - Caguana Baño, Johanna Michelle (2022)
The research was made with the improving purpose the soil physical and chemical characteristics, whose general aim was to assess organic mulch four types to recover eroded soils into beet (Beta vulgaris L.) cultivation in the Salache sector, Latacunga canton, Cotopaxi province. It was applied a DBCA Randomized Complete Block Design, arranged into strips (bank terraces), with 5 treatments including the control and 5 repetitions, for a 25 experimental units total. The results determined greater effectiveness in T3 (rice husk) based on indicators, such as: adapted seedlings number (99%), plant height (14.76 cm), leaves number (12), soil moisture (12, 4 cb), tuber diameter (20.46 mm), weight with leaves (26.1 gr), weight without leaves (11.98 gr) and for the weed case index both in quantity (2.8), height (4.74 cm), abundance (18.19%) and dominance (8.61) their means express, which this mulch type adapts very well to beet cultivation. However, into soil chemical characteristics, the best results are T1 (coal), since the pH decreased to 9.05; it increases macronutrients N (6.7 ppm); P (82 ppm) and K (4.09 meq/100g) and micronutrients B (2.28 ppm); Zn (2.4 ppm) and Cu (3.7 ppm); organic matter (0.71), improved soil texture and physical characteristics, increasing field capacity (26.3%); however, T3 (rice husk) it gets the first places, both in mesonutrients Ca (20.69 meq/100g), Mg (3.87meq/100g) and S (25 ppm); gravimetric humidity (20.4%) this due to the said material composition. At the end, the best benefit cost was T3 (rice husk) with a $6.67 value, which was set as an alternative for farmers into the soil conservation